Application of Ujrah Discounts on Pawn Products at BSI Kc Bojonegoro According To Sharia Economic Law - Milda Al Baqiyyatus Sholihah; Achmad Yasin (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
This research focuses on the application of ujrah discounts in pawn products implemented by Bank Syariah Indonesia (BSI) Bojonegoro Branch Office and analyzes its conformity with the principles of Sharia Economic Law. Sharia pawning, as one of the superior products of sharia banking, involves a contract between the bank and the customer where the customer hands over goods as collateral for the loan provided by the bank. In this agreement, the bank charges an ujrah fee in exchange for storage and maintenance services for collateral. However, with increasingly tight competition between sharia financial institutions, BSI KC Bojonegoro developed a marketing strategy in the form of providing discounts on ujrah fees applied. The research method used is qualitative-descriptive with data collection techniques through interviews, observation and documentation. The research results show that providing ujrah discounts at BSI KC Bojonegoro is carried out as a marketing strategy to attract customers and increase competitiveness. From the perspective of Sharia Economic Law, the application of this discount is considered in accordance with sharia principles as long as it does not violate the terms of the contract and transparency is maintained.